The long non-coding RNA ASMTL-AS1 promotes hepatocellular carcinoma progression by sponging miR-1343-3p that suppresses LAMC1 (laminin subunit gamma 1). Issue 1 (1st January 2022) - Mou, Yanjie; Sun, Qinguo
ABSTRACT: Long non-coding RNAs (lncRNAs) are critical regulators of hepatocellular carcinoma (HCC) carcinogenesis and development. We aimed to identify the function of the lncRNA ASMTL-AS1 during HCC malignancy. The expression of ASMTL-AS1, miR-1343-3p, and LAMC1 (laminin subunit gamma 1) was assessed in HCC tissues and cells. Cell Counting Kit-8 (CCK8) and Transwell migration assays were performed to determine the effect of ASMTL-AS1 on HCC cell proliferation and migration. Cell apoptosis was identified by detecting Bax and Bcl-2 protein expression using Western blotting, and a xenograft assay was performed to investigate tumor growth in vivo . The interplay between miR-1343-3p and ASMTL-AS1 or LAMC1 was verified through luciferase reporter and RNA immunoprecipitation assays. ASMTL-AS1 and LAMC1 were highly expressed in HCC tissues and cells, whereas miR-1343-3p showed low expression. Clinically, miR-1343-3p expression in HCC tissues showed a negative correlation with ASMTL-AS1 or LAMC1 expression. Functional assays demonstrated that ASMTL-AS1 silencing suppressed HCC cell proliferation and migration and increased cell apoptosis. More interestingly, ASMTL-AS1 sponged miR-1343-3p and miR-1343-3p to target the 3ʹ-UTR of LAMC1, thereby interfering with the malignant behavior of HCC cells. In conclusion, ASMTL-AS1 acts as a carcinogen in HCC through competing endogenous RNA (ceRNA) activity in the miR-1343-3p/LAMC1 axis. Our findings demonstrate that regulating ASMTL-AS1/miR-1343-3p/LAMC1-mediated HCC cell malignancy might be an effective method to interfere with HCC progression.